Application of the Example Non Example Cooperative Learning Model to the Biology Learning Outcomes of Class XI MIPA Students at SMA Negeri 26 Bone - Mursalim Mursalim; Erwing Erwing; Romi Adiansyah (Magister Pendidikan Biologi, Universitas Negeri Medan, 2023)
Students have difficulty solving a problem if they are not given visual learning stimuli, causing their analytical skills to be minimal. This study aims to describe the application of the Example Non Example cooperative learning model to the biology learning outcomes of class XI MIPA students at SMA Negeri 26 Bone. This research is quantitative research with a pre-experimental type of research with a one group pre-test and post-test design . The processed data is data on the number of population and student samples , pre-test and post-test learning outcomes, documentation, using a sampling technique that is purposive sampling with a sample of class XI MIPA 1 totaling 30 students. The research results obtained a significance value for paired sample t test pre-test post-test data of 0.000. Because the significance value is <0.05, it can be concluded that between the Pre-test and Post-test data there is a significant effect on the difference in treatment of each variable. This, the use of the example non example cooperative learning model can influence student learning outcomes.